Rarecare: A policy perspective on the burden of rare diseases on caregivers in Latin America - Dias, Ariadne Guimarães; Daher, Antoine; Barrera Ortiz, Lucy; Carreño-Moreno, Sonia; Hafez H, Sylvia R.; Jansen, Angela Marie; Rico-Restrepo, Mariana; Chaparro-Diaz, Lorena (Frontiers in Public Health, 2023)
In Latin America (LA), 40–50 million people live with rare diseases (RDs) that require constant monitoring, care, and attention. Caregivers help them with their basic life activities and medication administration, which they would otherwise be unable to perform. Family caregivers complement healthcare and social security systems; however, their unpaid work is often underappreciated and under-protected. Recognizing the need to address these unrecognized and undervalued women, the Americas Health Foundation (AHF) convened a panel of LA experts on caregiving for people with RDs to provide recommendations to support the undervalued family caregivers. A panel of LA experts in caregiving for RDs were given questions to address the challenges faced by family caregivers of people with RDs in LA. During a 3-day conference, the panelists' responses were discussed and edited until the panel agreed on recommendations to address the challenges. The identified challenges for caregivers included physical, emotional, and economical areas. Caregivers, primarily women, experienced physical pain, and social isolation, and were forced to pay substantial out-of-pocket expenses in their caregiving roles. Brazil and Colombia are at the forefront of policies to protect caregivers and their experiences in attempting to provide for this group are outlined as case studies for what is possible in LA. Finally, recognizing that caregivers must be included in formulating, executing, and evaluating care policies for people living with RDs and that the caregivers themselves require social assurances, the panel suggested policy objectives aimed at protecting caregivers of people living with RDs. The recommendations ranged from recognizing the role of the family caregiver as an essential supplement to the formal healthcare system to providing financial assistance, training, and workplace protection, among others. Finally, monitoring and evaluating the impact of policies is necessary to ensure that LA is moving forward in caring for family caregivers for people with RDs.